Sociocultural approach to learning English language at a higher educational institution (Pedagogy of Higher and Secondary Education, 2019)
Pokornaya L. N. Sociocultural approach to learning English language at a higher educational institution.In the article the analysis of peculiarities of communication competence formation gives the possibility to identify sociocultural competence of future English teachers as a separate component of the communication competence and to consider it as an integral system consisting of the following competences: country studies, linguistic and cultural studies and sociolinguistic.
Keywords: communication competence; sociocultural competence; country studies competence; linguistic and cultural country studies competence; sociolinguistic competence